Assessing an experimental rule change in the pay-offs for soccer league match outcomes using historical data for Ireland - Dargahi, Shilan; Reilly, Barry (Frontiers in Behavioral Economics, 2024)
IntroductionThis paper evaluates an experimental rule change trialed in the League of Ireland for one season in the early 1980s, where four points were awarded for an away win, three for a home win, two for an away draw, and one for a home draw. This pay-off structure was designed to incentivize visiting teams to engage in more offensive play, thus potentially increasing the number of goals scored per game and reducing the incidence of drawn games.MethodsUsing match-level data for six playing seasons, the impact of this reward scheme on an array of match-level outcomes is evaluated using an array of fixed effects regression models.Results and discussionThe key empirical findings suggest this change to the pay-off structure did not reduce the drawn game rate but did induce a modest increase in the average goal scoring of the home team with subsequent implications for average goal difference. The absence of an effect for the visiting team is rationalized in terms of prospect theory, and the asymmetric implication of the policy change for the respective loss aversion parameters of the home and the visiting teams. In addition, we also use a lottery framework to further demonstrate why the short-lived pay-off structure failed in its primary objective to incentivize visiting teams to engage in more offensive play.